2023
DOI: 10.1021/acs.inorgchem.3c00905
|View full text |Cite
|
Sign up to set email alerts
|

Tunable White Light Emission of a Metal–Organic Framework Based on a Bisquinoxaline Derivative by Introducing Red–Green Cationic Dyes

Abstract: The unique structural advantages give metal−organic frameworks (MOFs) a special use as host substrates to encapsulate organic dyes, which would result in specific host−guest composites for white-light phosphors. In this work, an anionic MOF exhibiting blue emission was constructed using bisquinoxaline derivatives as photoactive centers, which could effectively encapsulate rhodamine B (Rh B) and acriflavine (AF) to form an In-MOF ⊃ Rh B/AF composite. By simply adjusting the amount of Rh B and AF, the emitting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…This revealed that the multicolor light emission of RhB x /FL 1-x @1 could be easily controlled by changing the relative contents of RhB and FL. [26] Finally, PXRD patterns of RhB x /FL 1-x @1 were consistent with the simulated 1 pattern, which indicated that the introduction of dye molecules did not destroy the structure (Figure S11).…”
Section: Structure Description Forsupporting
confidence: 70%
“…This revealed that the multicolor light emission of RhB x /FL 1-x @1 could be easily controlled by changing the relative contents of RhB and FL. [26] Finally, PXRD patterns of RhB x /FL 1-x @1 were consistent with the simulated 1 pattern, which indicated that the introduction of dye molecules did not destroy the structure (Figure S11).…”
Section: Structure Description Forsupporting
confidence: 70%